The effect of application of tea waste (Camellia sinensis) fermented with Aspergillus niger on broiler - Krisnan, Rantan (Indonesian Journal of Animal and Veterinary Sciences, 2005)
The purpose of this experiment is to find out the effect of Aspergillus niger fermented tea waste (Camellia sinensis) in feed on body weight gain, protein efficiency and percentage of carcass of broiler. The experiment was conducted in a Completely Randomized Design using 100 day old chicks (DOC) Avian CP-707 strain. The animal were devided into five treatments of ration. Each treatment was replicated four times. All dietary treatment were formulated based on fermented tea-waste content, namely: RO (0.0%), R1 (2.5%), R2 (5.0%), R3 (7.5%), and R4 (10.0%). The results indicated that broilers gave the best responses to the R1 (2.5% fermented tea-waste) to all measured parameters. Positive responses also observed in broilers given ration containing fermented tea-waste up to the level 7.5%, however, at the level 10.0% decreased body weight gain, but the protein efficiency and the carcass percentage were equal to the R0 (control ration). Â Â Key Words: Fermented Tea-Waste, Body Weight Gain, Protein Efficiency, Carcass, Broiler